The severity of coronary heart disease and the incidence of later diabetic retinopathy in diabetic population: A retrospective cohort study - Ke-Hsin Ting; Po-Jen Yang; Jing-Yang Huang; Chia-Yi Lee; Shih-Chi Su; Shun-Fa Yang (PLoS ONE, 2025)
Objectives The coronary heart disease (CHD) can influence the development of several diseases. The presence of CHD is correlated to a higher incidence of concurrent diabetic retinopathy (DR) in previous study. Herein, we aim to analyze the relationship between the CHD severity and following DR with different severity. Methods A retrospective cohort study was conducted with the usage of Taiwan National Health Insurance Research Database (NHIRD). The CHD patients with DM were categorized into those with medical treatments and those received percutaneous coronary intervention (PCI) management with a 1:1 ratio. The major outcome was the development of DR, diabetic macular edema (DME) and proliferative diabetic retinopathy (PDR) 6 months after the onset of CHD. Results There was 7317, 316, and 386 episodes of DR, DME and PDR in the mild CHD groups and 8568, 411, and 508 events of DR, DME and PDR in the severe CHD groups, respectively. The severe CHD group showed a significantly higher incidence of DR (aHR: 1.063, 95% CI: 1.038–1.089, P = 0.0324), DME (aHR: 1.412, 95% CI: 1.252–1.594, P = 0.0092) and PDR (aHR: 1.314, 95% CI: 1.172–1.473, P = 0.0113) compared to the mild CHD group. The cumulative incidence of DR was significantly higher in the severe CHD group (P < 0.001). In the subgroup analysis, the association between CHD severity and DR was more prominent in the female population (P = 0.0224). Conclusions The severe CHD is associated with higher incidence of following DR, DME and PDR, while the incidence of DR in CHD is positively correlated to longer disease period.